Active Targeting of Dendritic Polyglycerols for Diagnostic Cancer Imaging. Issue 7 (26th December 2019) - Pant, Kritee; Neuber, Christin; Zarschler, Kristof; Wodtke, Johanna; Meister, Sebastian; Haag, Rainer; Pietzsch, Jens; Stephan, Holger
Abstract: Active tumor targeting involves the decoration of nanomaterials (NMs) with oncotropic vector biomolecules that selectively recognize certain antigens on malignant cells or in the tumor microenvironment. This strategy can facilitate intracellular uptake of NM through specific interactions such as receptor‐mediated endocytosis and can lead to prolonged retention in the malignant tissues by preventing rapid efflux from the tumor. Here, the design of actively targeting, renally excretible bimodal dendritic polyglycerols (dPGs) for diagnostic cancer imaging is described. Single‐domain antibodies (sdAbs) specifically binding to the epidermal growth factor receptor (EGFR) are employed herein as targeting warheads owing to their small size and high affinity for their corresponding antigen. The dPGs equipped with EGFR‐targeting feature are compared head‐to‐head with their nontargeting counterparts in terms of interaction with EGFR‐overexpressing cells in vitro as well as accumulation at receptor‐positive tumors in vivo. Experimental results reveal a higher specificity and preferential tumor accumulation for the α‐EGFR dPGs, resulting from the introduction of active targeting capabilities on their backbone. These results highlight the potential for improving the tumor uptake properties of dPGs by strategic use of sdAb functionalization, which can ultimately prove useful to the development of ultrasmall NM with highly specific tumor accumulation. Abstract : Small, but hitting the target: epidermal growth factor receptor (EGFR) targeted, renally excretible bimodal probes based on ultrasmall dendritic polyglycerols and high‐affinity single‐domain antibodies for diagnostic cancer imaging are created. Compared to the nontargeted analog, it shows higher specificity for EGFR‐positive cells and superior overall tumor accumulation in murine xenografts.